1986
DOI: 10.1149/1.2148707
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Distribution of Nickel Hydroxide in Sintered Nickel Plaques Measured by Radiotracer Method during Electroimpregnation” [J. Electrochem. Soc., 133, 17]

Abstract: Term Atmospheric Oxidation of High Purity Iron," Frankenthal et al. report that (i) pure iron in a stoppered bottle maintained a bright finish over a long period (years), (it) there have been no reports of the passivation of iron in the atmosphere for periods longer than several weeks, (iii) the oxide film thickness, with a correction for contamination, after twenty years was no more than 5-6 nm, and (iv) there is a similarity between passivation in air and film growth in solution (anodic oxidation).We should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…SFt vvg = 1-e w~ .... [10] Wg,max .... is the maximum loading capacity, which can be estimated from the density of Ni(OH)2, pj Wg .... = pj [11] However, the experimental results indicate that the actual maximum loadLag level is lower than the density of Ni(OH)2, 4.15 g/cm 3, due to the filling of the porous electrode and the plugging of the pores. Figure 8 compares the experimental data with the theoretical loading curves predicted by Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SFt vvg = 1-e w~ .... [10] Wg,max .... is the maximum loading capacity, which can be estimated from the density of Ni(OH)2, pj Wg .... = pj [11] However, the experimental results indicate that the actual maximum loadLag level is lower than the density of Ni(OH)2, 4.15 g/cm 3, due to the filling of the porous electrode and the plugging of the pores. Figure 8 compares the experimental data with the theoretical loading curves predicted by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…preparing nickel hydroxide electrodes presently being used in nickel-cadmium, nickel-zinc, and nickel-hydrogen batteries (1)(2)(3). Despite the fact that there are several advantages of this method over the conventional chemical impregnation method (4)(5)(6)(7)(8)(9)(10), the conditions of the process have been experimentally determined so far through trial and error procedures. There is a need to apply the principles of electrochemical engineering in order to establish the conditions which would lead to a process competitive from both economics and quality considerations.…”
Section: Fig 1 Schematic Representation Of Electrochemical Precipitat...mentioning
confidence: 99%
“…It is suggested that by a careful selection of the flow rate, flow direction, and electrode configuration, optimum conditions for the fabrication of nickel hydroxide electrodes can be achieved. Manuscript submitted Feb. 6,1989; revised manuscript received June 20, 1989.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…onstrated that at low and high frequency, the diffusional impedance at a sinusoidal electrode shows the same proportionality to frequency as the planar electrode, but for intermediate values the functional behavior is more complex; in this range, the magnitude is not proportional to ~-1/2 and the phase lag is frequency dependent. To develop these calculations, we utilize a perturbation solution to the transient-diffusion equation for the concentration field, originally presented to calculate the Cottrell-like current on the sinusoidal surface (6), with the perturbation parameter being the ratio of the amplitude-to-period length, A. The accuracy and limitation of the perturbation solution for the diffusional impedance is determined and the error is shown to be less than 2% for moderate wall oscillation amplitude (A < 0.15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation